The potency of the efficiency and compression rate of Cirebon language script using the Binary Huffman algorithm. Issue 4 (March 2021) - Ismail, N; Yusuf, T; Fajar, R; Alqinsi, P; Kodir, A; Qodim, H
Abstract: Each language usually has several important features that are hidden statistically and certain redundancy. These features can be utilized to perform text compression that is suitable for the optimal use of resources. This study proposes an analysis the potency of the efficiency and compression rate of Cirebon language script using the Binary Huffman algorithm. The analysis of the potency is based on the entropy of the Cirebon language script. The study begins with an analysis of the Cirebon language script to calculate the probability of each symbol. These probabilities are used to calculate the value of entropy. The results showed that the entropy of the Cirebon language script was 3.976 bits per symbol, with an expected code length of 4.02 bits per symbol. Then, the estimated efficiency of compression with the Binary Huffman Code is 98.89% and the compression rate is 0.80402. These results can be considered in the use of Cirebon language compression for the telecommunications transmission process.